Peran Kepala Desa Dalam Pelaksanaan Pembangunan Menurut Undang-Undang Desa dan Fiqh Siyasah; Studi Kasus Desa Mekarjati Kecamatan Haurgeulis Kabupaten Indramayu - Susanto Susanto; Abdur Rahim (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
The performance of a village head as head of village government must be able to carry out its main duties, namely leading and coordinating the village administration in implementing village development. The role of the village head is one aspect that stands out and affects the success of village development. The village head is assisted by village officials, as an element of village government administration. The formulation of the problem in this research is